2018
DOI: 10.1155/2018/5419861
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness, and Control of Hypertension in Greater Beirut Area, Lebanon

Abstract: Background Hypertension (HTN) has been identified as the leading risk factor for mortality and the third cause of disability worldwide. Lebanon has witnessed a threefold increase in the prevalence of HTN in the past decade. The timely exploration and detection of the factors contributing to a higher prevalence of the disease among the Lebanese population is fundamental. The objectives of this study were to assess the prevalence, awareness, and control rates of HTN in Greater Beirut Area in Lebanon and to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
(52 reference statements)
5
14
1
Order By: Relevance
“…These results are in line with previous evidence from the literature that shows an increasing trend in hypertension prevalence among the general adult population with a higher burden among women, notably in the 70 + age‐group 3‐5 . A possible explanation is the reduction in health care seeking behavior among women toward older age and, thus, a decrease in their hypertension management and control 11 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with previous evidence from the literature that shows an increasing trend in hypertension prevalence among the general adult population with a higher burden among women, notably in the 70 + age‐group 3‐5 . A possible explanation is the reduction in health care seeking behavior among women toward older age and, thus, a decrease in their hypertension management and control 11 .…”
Section: Discussionsupporting
confidence: 91%
“…In Arab countries, such as Lebanon, where the increase in the proportion of older adults is prominent, knowledge about hypertension prevalence and control is limited in the absence of updated national registries. Nonetheless, available evidence shows an increasing prevalence of hypertension throughout the years and low levels of awareness and control in the general Lebanese adult population 3‐5 . With the lack of data from an exclusive elderly population, the re‐examination of the burden of hypertension and the level of management of the disease is needed to allow for better prevention.…”
Section: Introductionmentioning
confidence: 99%
“…It was disagreed with the results from other studies [28,29], this study showed that female hypertension patients had lower effective awareness and treatment rate of BP than their male counterparts. We hypothesized that women in this group had low social status owing to their traditional customs.…”
Section: Discussioncontrasting
confidence: 99%
“…Maybe the high prevalence of the disease in their families helps them to better understand hypertension and prompts them to be more proactive in treating it. This trend was also mentioned in the Lebanon population in 2018 [29].…”
Section: Discussionsupporting
confidence: 62%
“…Global data show that control of blood pressure is poor (7-9) especially in low-and middle-income countries (LMICs) with a recent review indicating that only 10% of hypertensive adults in LMICs have their blood pressure under control (10). In Arab countries, less than third of hypertensive patients have controlled blood pressure, according to a recent review (11), and in Lebanon, a middle-income country of the Arab region (12), control rates are suboptimal and comparable to the regional average (10,13,14).…”
Section: Introductionmentioning
confidence: 99%